2016
DOI: 10.1039/c6ce00263c
|View full text |Cite
|
Sign up to set email alerts
|

Role of polymers in solution and tablet-based carbamazepine cocrystal formulations

Abstract: The aim of this study was to evaluate the influence of three chemically diverse polymers of Hydroxypropylemthylcellulose acetate succinate (HPMCAS), Polyvinylpyrrolidone (PVP) and PolyEthylene Glycol (PEG) on the phase transformation of three carbamazepine (CBZ) cocrystals of carbamazepine-nicotinamide (CBZ-NIC), carbamazepine-saccharin (CBZ-SAC) and carbamazepine-cinnamic acid (CBZ-CIN) in solution and tablet based formulations. Ba sed on the solubility and powder dissolution studies, it demonstrates that coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 26 publications
2
40
2
Order By: Relevance
“…Indeed, rapid conversion of the cocrystals into pure drug was demonstrated by PXRD analysis of the solids recovered after the dissolution tests in short time periods (~1-5 min, Figure 3). A similar behavior has been documented for other cocrystal phases in the literature [24,25,30,36,37,[55][56][57]. For example, exemestane-maleic-acid cocrystals did not increase solubilization of the drug due to rapid phase transformation [55].…”
Section: Performance Of Ntz Cocrystals Under Non-sink Conditionssupporting
confidence: 77%
See 3 more Smart Citations
“…Indeed, rapid conversion of the cocrystals into pure drug was demonstrated by PXRD analysis of the solids recovered after the dissolution tests in short time periods (~1-5 min, Figure 3). A similar behavior has been documented for other cocrystal phases in the literature [24,25,30,36,37,[55][56][57]. For example, exemestane-maleic-acid cocrystals did not increase solubilization of the drug due to rapid phase transformation [55].…”
Section: Performance Of Ntz Cocrystals Under Non-sink Conditionssupporting
confidence: 77%
“…The dissolution performance of the formulated solid samples was analyzed by means of powder dissolution tests using the USP 1 (basket) apparatus. A similar strategy was employed for the evaluation of formulated cocrystals of carbamazepine [29,30]. The dissolution profiles in pH 7.5 PBS for NTZ in pure form, a 2:1 stoichiometric physical mixture of NTZ and SUC, and NTZ-SUC (2:1) cocrystals formulated with an increasing amount of Methocel ® 60 HG are given in Figure 6.…”
Section: Usp 1 Apparatus Powder Dissolution Experiments Of Formulatiomentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In order to maximise the potential of cocrystals, it is critical to include inhibitors in a formulation to prevent or delay the precipitation of the parent drug during dissolution. [7][8][9][10][11][12][13] Although polymeric crystallization inhibitors have been extensively studied in many other systems, in particular amorphous solid dispersions, 14,15 such studies are still rare for cocrystal based formulations. In a recent study, we have found that the competition of intermolecular hydrogen bonding among drug/coformer, drug/polymer, and coformer/polymer was a key factor responsible for maintaining the supersaturation through nucleation inhibition and crystal growth modification in a supersaturated cocrystal solution with a pre-dissolved polymer.…”
Section: Introductionmentioning
confidence: 99%